The Use of Election Observation Reports in Regional Human Rights Jurisprudence. Issue 4 (1st October 2016) - Suksi, Markku
ABSTRACT: This article argues that reports from election observation missions can constitute evidence and shows that they are occasionally being used as evidence when regional human rights bodies are resolving human rights cases that deal with elections. The practice has so far been confined to regional human rights jurisprudence. Between 1998 and April 2016, election observation mission reports have been used in a total of 16 cases brought before regional human rights courts and commissions. The African Commission on Human and Peoples' Rights and the Inter-American Court of Human Rights have each used mission reports once, while the main bulk of practice has emerged in the European Court of Human Rights (ECtHR). I will argue that so far, the jurisprudence indicates three different usages of election mission reports: (1) as facts in the circumstances of the case; (2) as corroborative or indirect evidence; and (3) as direct evidence that is conclusive for the resolution of the case. Furthermore, there is an emerging dialogue between the ECtHR and the Organization for Security and Co-operation in Europe–Office for Democratic Institutions and Human Rights (OSCE/ODIHR), particularly with regards to the election observation missions that concern Article 3 of the First Protocol to the European Convention on Human Rights. This indicates that there may be a new function for mission reports in human rights law, particularly in Europe.